Analyzing Game-Based Learning Approaches in Brazilian Schools - Bruna Costa; Rafaela Lima; Thiago Rocha (Journal Emerging Technologies in Education, 2024)
Background. Game-based learning (GBL) has become an innovative pedagogical approach, integrating gaming elements into educational contexts to enhance student engagement, motivation, and learning outcomes. In Brazil, the adoption of GBL in schools is growing, yet its impact on student learning, particularly in diverse educational settings, remains underexplored.Purpose. This study aims to analyze the effectiveness of game-based learning approaches in Brazilian schools, focusing on their influence on student engagement, knowledge retention, and academic performance across various subjects.Method. A mixed-methods approach was employed, combining quantitative data from pre- and post-assessments with qualitative insights from teacher interviews and student surveys. A sample of 400 students and 20 teachers from five Brazilian schools participated in the study, using educational games in classrooms for a period of three months.Result. The findings indicate that GBL significantly increased student engagement and motivation, with 78% of students reporting improved interest in the subjects taught through games. Additionally, students in the GBL group showed a 15% improvement in post-assessment scores compared to those taught using traditional methods. Teachers noted that GBL provided a more interactive and enjoyable learning experience, fostering better classroom participation.Conclus. Game-based learning can effectively enhance student engagement and academic performance in Brazilian schools. The findings suggest that integrating GBL into curricula could contribute to more dynamic and impactful learning environments.